2019
DOI: 10.1101/541201
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutagenesis oforcoimpairs foraging but not oviposition in the hawkmothManduca sexta

Abstract: Plant volatile detection through olfaction plays a crucial role in insect behaviors. In vivo, the odorant receptor co-receptor orco is an obligatory component for the function of odorant receptors (ORs), a major receptor family involved in insect olfaction. We used CRISPR-Cas9 targeted mutagenesis to knock-out (KO) orco in a neurophysiological model species, the hawkmoth Manduca sexta. M. sexta and its host, the Sacred Datura (Datura wrightii) share a model insect-plant relationship based on mutualistic and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 120 publications
0
3
0
Order By: Relevance
“…Plants produce complex chemical mixtures, and herbivores likely combine many of these chemicals to make appropriate foraging decisions (11,12,29). In line with this idea, recent in vivo work shows that, while individual compound classes and insect gustatory receptors can be of major importance for specific behavioral patterns, their disruption is not sufficient to fully suppress these behaviors (22)(23)(24). In the case of the western corn rootworm, we find that even the suppression of two major foraging cues does not fully abolish its ability to find and accept a host plant, at least under laboratory conditions.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Plants produce complex chemical mixtures, and herbivores likely combine many of these chemicals to make appropriate foraging decisions (11,12,29). In line with this idea, recent in vivo work shows that, while individual compound classes and insect gustatory receptors can be of major importance for specific behavioral patterns, their disruption is not sufficient to fully suppress these behaviors (22)(23)(24). In the case of the western corn rootworm, we find that even the suppression of two major foraging cues does not fully abolish its ability to find and accept a host plant, at least under laboratory conditions.…”
Section: Discussionmentioning
confidence: 96%
“…Over the past decades, herbivores have been found to respond to a multitude of plant primary and secondary metabolites in artificial diet experiments (13,16,17). An increasing number of studies now also document the importance of these metabolites in planta through molecular manipulative approaches (20)(21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…Their results suggested that ionotropic responses are followed by membrane depolarization and, ultimately, metabotropic responses are unleashed. More recently, the use of CRISPR-Cas9 to disrupt the expression of Orco in the hawkmoth M. sexta showed that Orco is crucial for sexual communication but not for host location ( Fandino et al, 2019 ). Despite all these advances based on model insects, the study of a non-model insect established a milestone in insect olfaction.…”
Section: Role Of Non-model Insects In the Study Of Olfactionmentioning
confidence: 99%